Sociological interpretations of health and salvation, and their theological relevance - Oviedo Torró, Lluís (Razón y fe, 2023)
We wonder whether the interaction between the idea of health and the more theologically oriented of salvation has changed in recent times, and to what extent the perceived changes have led to rethinking the relationship between science and religious faith. Firstly, a review of a trend in studies on religion and health shows, on the one hand, their great profusion and the results that point to a generally positive influence of one variable on the other. On the other hand, these studies invite us to rethink some analyses in the sociology of religion, concerning its role and persistence in secularised societies, as well as its more decidedly “religious” character. It seems that such changes affect the relationship between science and faith, which can claim a much more concrete and empirical discourse, i.e. the possibility of speaking a common language with science.